Co-synthesis of methanol and methyl formate from CO2 hydrogenation over oxalate ligand functionalized ZSM-5 supported Cu/ZnO catalyst - Ayodele, O.B. (Elsevier Ltd, 2017)
Graphical abstract: Co-synthesis of methanol and methyl formate (MF) was achieved in this study using expediently synthesized ZSM-5 supported oxalate ligand functionalized Cu/ZnO catalyst (CZOx/Z) in a continuous flow reactor. The catalyst characterization results showed that the synthesis protocol via oxalate ligand functionalization (OLF) achieved considerable reduction of CuO→Cu2O→Cu leading to highly reducible active metals with largely weak metal-support-interactions according to the X-ray photoelectron spectroscopy, Raman spectroscopy and temperature programmed reduction. The ZnO reduction peak was also observed to shift to lower reduction temperature. Furthermore, the NH3- and CO2- temperature programmed desorption studies showed that CZOx/Z has both acid and basic sites, but the acid sites were about four times higher. These qualities were ascribed to the OLF at the synthesis stage which also guarantees ultrafine active metal particle sizes with high degree of dispersion. The CZOx/Z showed exceptional CO2 hydrogenation activity at 250°C and 2.25MPa, the initial CO2 conversion increased marginally from 15.5 to 15.9 in the first 180min and increased to 20.5 at 600min time-on-stream. The increment was ascribed to reduction of remnant unreduced active metal species with methanol which simultaneously proceeds with dehydrogenation of produced methanol to form MF promoted by the acid sites. The methanol selectivity was 97.16 at 60min TOS and later decreased to 64.64 at 180min as the formation of MF increased owing to the progressive reduction of active metals with formed methanol. CZOx/Z is a promising catalyst for co-synthesis of methanol and MF. © 2016 Elsevier Ltd. All rights reserved.